Causes of Mortality in Korean Patients with Neurodegenerative Dementia. (25th April 2022) - Choi, Hyo Geun; Park, Bumjung; Kim, Ji Hee; Kim, Joo-Hee; Kwon, Mi Jung; Kim, Miyoung
Abstract : The prevalence of neurodegenerative dementia is increasing owing to the rapid growth of the older population. We investigated risks and causes of mortality in Korean patients with neurodegenerative dementia using data from the Korean Health Insurance Review and Assessment Service-National Sample Cohort with the aim to improve their care. From a pool of 1, 125, 691 patients, 11, 215 patients aged ≥60 years who were diagnosed with dementia between 2002 and 2013 were examined along with 44, 860 matched controls. A Cox proportional hazard model was used to calculate crude and adjusted hazard ratios (HRs). During the follow-up period, 34.5% and 18.8% of individuals in the neurodegenerative dementia and control groups, respectively, died (P < 0.001 ). The adjusted HR for mortality in the neurodegenerative dementia group was 2.11 (2.41 and 1.96 in men and women, respectively). Moreover, the adjusted HRs in patients with neurodegenerative dementia were 3.25, 2.77, and 1.84 for those diagnosed at ages 60–69, 70–79, and ≥80 years, respectively. The highest odds ratio for mortality was noted among patients with neurologic disease (15.93) followed by those with mental disease (4.89). These data show that the risk of mortality increased regardless of age and sex in Korean patients with neurodegenerative dementia.